2015
DOI: 10.3944/aott.2015.14.0451
|View full text |Cite
|
Sign up to set email alerts
|

Operative vs. nonoperative treatment for comminuted proximal humeral fractures in elderly patients: a current meta-analysis

Abstract: Compared with operative treatment for closed comminuted proximal humeral fractures in elderly patients, conservative treatment can effectively reduce the risk of additional surgeries and complications. However, there is no statistical difference between operative and nonoperative treatment in terms of clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…Non-displaced fractures can be successfully treated non-operatively [21], whereas optimal treatment for displaced fractures is more controversial and includes surgical and conservative management approaches. It is unclear which patients stand to benefit the most from surgical treatment [22], and surgery is associated with higher costs [23, 24], surgical and medical complications, and additional revision surgery [25] compared to conservative treatment. Traditional surgical approaches for treating PHF in the elderly included hemiarthroplasty and open reduction and internal fixation (ORIF).…”
Section: Introductionmentioning
confidence: 99%
“…Non-displaced fractures can be successfully treated non-operatively [21], whereas optimal treatment for displaced fractures is more controversial and includes surgical and conservative management approaches. It is unclear which patients stand to benefit the most from surgical treatment [22], and surgery is associated with higher costs [23, 24], surgical and medical complications, and additional revision surgery [25] compared to conservative treatment. Traditional surgical approaches for treating PHF in the elderly included hemiarthroplasty and open reduction and internal fixation (ORIF).…”
Section: Introductionmentioning
confidence: 99%
“…Only one patient reported a complication (surgical wound dehiscence), which could have been attributed this to the small sample included in the study. (25), this study suggests that the conservative approach leads to good clinical results and bone healing, and that it furthermore avoids the risks associated with surgery.…”
Section: Proximal Humeral Fracturesmentioning
confidence: 64%
“…There is debate on operative versus non-operative treatment for proximal humeral fractures. Some previous studies have reported that patients undergoing operative treatment are more likely to have complications [6, 8, 9] and that no significant difference exists in outcomes after operative and non-operative treatment [5, 7]. Although our study was not designed to assess comparative-effectiveness of operative versus non-operative treatments for proximal humeral fractures, it provides data on complications, readmissions, in-hospital mortality, and time to revision surgery after non-operative treatment, ORIF, and arthroplasty.…”
Section: Discussionmentioning
confidence: 99%